Nilai-nilai pendidikan kedisiplinan dalam perspektif surat Al-Ashr - Surono; Uswatun Khasanah; Meti Fatimah (At Turots: Jurnal Pendidikan Islam, 2023)
The Qur'an is a Muslim's guide to life. One of the most monumental surahs of the Qur'an is Surah Al-'Ashr. The focus of this study is on the understanding of Surat Al-'Ashr which contains the concept of operation and principles of discipline in Islamic schools. The purpose of this study is to find out: 1) What is the value of teaching about disciplinary morals contained in Surah Al-Ashr? This type of research is a literature search. The subject matter is the concept of discipline from the point of view of Surah Al-'Ashr. The sources of information are the Quran and books, magazines and other writings that support it. The data collection methods used are documentary method and Maudhu'i method. Data validity uses source triangulation techniques. In addition, the material is analyzed using the interpretative method. The results of the study show that Surah Al 'ashr can be transformed into verses that show the concept of discipline in Islam, namely: time and faith. First, he must be good at managing/disciplining time well, while faith must be applied in the form of righteous deeds, amar ma'ruf, and patience. In doing charity, one must recognize Mujahada, Muraqaba, Muhasabah, Muaqobah and Istiqomah. The concept of discipline in the view of Surah Al'Ashr which the author concludes following the views of the mufassirin scholars is: Discipline in the sense of temporary consistency, trustworthiness, charity, mutual advice and patience.